EFFECTS OF THE VIBRATIONS OF POWERED HAND TOOLS ON USERS: A CASE STUDY - Kolawole, Adekunle; Ikubanni, Peter Pelumi; Adeboye, Adegoke Sanyaolu (Journal of Applied Engineering Science, 2020)
Powered hand tools reduce the time spent on tasks; however, they generate vibrations which may pose significant risk to operators’ health. In this study the impact of power hand tools on users was considered. Five basic power hand tools were identified and the impact of vibration was assessed on users. Digital vibration meter was used to measure the vibration produced on five operators while operating the identified power tools. Values obtained from each operator were imputed to the hand-arm vibration calculator to determine daily exposure limit and total exposure point for each of them. Results obtained indicate daily exposure limit of 4.08, 11.64, 21.06, 46.96 and 62.36 m/s2; and average total exposure point of 261, 2242, 7107, 35436, and 63781; for hand milling machine, hand drilling machine, grinding machine, hand mower, and lawn mower respectively. Among the power tools examined, it is only the exposure vibration from hand milling machine that was within the recommended acceptable daily exposure limit of 5 m/s2 and total exposure point of 400. Measures were suggested to lessen the exposure time and vibration magnitude the operators are exposed to so as to reduce the probability of hand-arm vibration syndrome (HAVS) among the operators.